2012
DOI: 10.1371/journal.pone.0038653
|View full text |Cite
|
Sign up to set email alerts
|

The First Illumina-Based De Novo Transcriptome Sequencing and Analysis of Safflower Flowers

Abstract: BackgroundThe safflower, Carthamus tinctorius L., is a worldwide oil crop, and its flowers, which have a high flavonoid content, are an important medicinal resource against cardiovascular disease in traditional medicine. Because the safflower has a large and complex genome, the development of its genomic resources has been delayed. Second-generation Illumina sequencing is now an efficient route for generating an enormous volume of sequences that can represent a large number of genes and their expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
84
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 45 publications
19
84
4
2
Order By: Relevance
“…The number of unigenes obtained from P. ternata was lower than that obtained from Carthamus tinctorius (120,778) (Lulin et al, 2012), Polygonum cuspidatum (86,418) (Hao et al, 2012), and Salvia miltiorrhiza (64,139) , However, the number of unigenes obtained from P. ternata was higher than that from Codonopsis pilosula (45,511) (Gao et al, 2015), and Isatis indigotica (36,367) (Chen et al, 2013). The average unigene length (611 bp) was slightly greater than that of other medicinal plants, including C. tinctorius (446 bp) (Lulin et al, 2012), S. miltiorrhiza (413 bp) , and P. cuspidatum (365 bp) (Hao et al, 2012). The unigene annotation rate observed in the present study (79.72%) was relatively higher.…”
Section: Ssr Discoverymentioning
confidence: 63%
“…The number of unigenes obtained from P. ternata was lower than that obtained from Carthamus tinctorius (120,778) (Lulin et al, 2012), Polygonum cuspidatum (86,418) (Hao et al, 2012), and Salvia miltiorrhiza (64,139) , However, the number of unigenes obtained from P. ternata was higher than that from Codonopsis pilosula (45,511) (Gao et al, 2015), and Isatis indigotica (36,367) (Chen et al, 2013). The average unigene length (611 bp) was slightly greater than that of other medicinal plants, including C. tinctorius (446 bp) (Lulin et al, 2012), S. miltiorrhiza (413 bp) , and P. cuspidatum (365 bp) (Hao et al, 2012). The unigene annotation rate observed in the present study (79.72%) was relatively higher.…”
Section: Ssr Discoverymentioning
confidence: 63%
“…The rate of reads with Q20-value reached 98.68%. Based on these reads, 96,149 unigenes were assembled with an average length of 973 bp, which was larger than the mean unigene lengths found in butterfly (197 bp;Vera et al, 2008), sweet potato (581 bp; Guo et al, 2011), Salvia miltiorrhiza (331 bp; Zhang et al, 2012), safflower (446 bp; Lulin et al, 2012), and wax gourd (709 bp; Jiang et al, 2013). We aligned the unigene sequences to the Nr, Swiss-Prot, GO, COG, and KEGG protein databases and found that most unigene sequences could be matched to unique protein sequences in the various databases.…”
Section: Discussionmentioning
confidence: 97%
“…Insight into the function of these genes and demonstration of their novelty may pilot to a better perception of the drought tolerance mechanisms in safflower and potentially other oilseed crops (Thippeswamy et al 2013). Lulin et al (2012) also conducted large-scale genomics, in order to investigate genes and pathways that may regulate flavonoids, the biosynthesis of unsaturated fatty acids (that can be beneficial to oxidative stress caused by abiotic stresses like drought), and other secondary metabolites in the safflower. Furthermore, these genes were moderately conserved in the safflower genome when compared to those of other plants.…”
Section: Functional Genomics For Drought Tolerancementioning
confidence: 99%